Single-cell analysis of innate spinal cord regeneration identifies intersecting modes of neuronal repair - Saraswathy, Vishnu Muraleedharan; Zhou, Lili; Mokalled, Mayssa H. (Nature communications, 2024)
Adult zebrafish have an innate ability to recover from severe spinal cord injury. Here, we report a comprehensive single nuclear RNA sequencing atlas that spans 6 weeks of regeneration. We identify cooperative roles for adult neurogenesis and neuronal plasticity during spinal cord repair. Neurogenesis of glutamatergic and GABAergic neurons restores the excitatory/inhibitory balance after injury. In addition, a transient population of injury-responsive neurons (iNeurons) show elevated plasticity 1 week post-injury. We found iNeurons are injury-surviving neurons that acquire a neuroblast-like gene expression signature after injury. CRISPR/Cas9 mutagenesis showed iNeurons are required for functional recovery and employ vesicular trafficking as an essential mechanism that underlies neuronal plasticity. This study provides a comprehensive resource of the cells and mechanisms that direct spinal cord regeneration and establishes zebrafish as a model of plasticity-driven neural repair. The roadmap to promote neural repair after spinal cord injury remains elusive. Here, longitudinal single-cell sequencing in adult zebrafish identifies intersecting modes of neuronal plasticity and neurogenesis during innate neural repair.